Lay perceptions of diabetes mellitus and prevention costs and benefits among adults undiagnosed with the condition in Singapore: a qualitative study - Jumana Hashim; Helen Elizabeth Smith; E Shyong Tai; Huso Yi (BMC, 2022)
Abstract Background Therapeutic lifestyle changes can reduce individual risk of type 2 diabetes (T2D) by up to 58%. In Singapore, rates of preventive practices were low, despite a high level of knowledge and awareness of T2D risk and prevention. The study explored the context of the discrepancy between knowledge and practices in T2D prevention among adults undiagnosed with the condition. Methods In-depth interviews with 41 adults explored lay beliefs of T2D and the sources of these perceptions, subjective interpretation of how T2D may impact lives, and perceived costs and benefits of practising preventative behaviours. Purposive sampling was used to maximise the variability of participants in demographic characteristics. Thematic analysis was conducted to identify themes related to the domains of inquiry. Results Participants' risk perceptions were influenced by familial, social, and cultural contexts of the representation and management of T2D conditions. The adverse effects of T2D were often narrated in food culture. The cost of adopting a healthy diet was perceived at a high cost of life pleasure derived from food consumption and social interactions. Inconveniences, loss of social functions, dependency and distress were the themes related to T2D management. Participants' motivation to preventive practices, such as exercise and weight loss, were influenced by short-term observable benefits. Conclusions T2D risk communication needs to be addressed in emotionally impactful and interpersonally salient ways to increase the urgency to adopt preventative behaviours. Shifting perceived benefits from long-term disease prevention to short-term observable wellbeing could reduce the response cost of healthy eating.